Major Grass Pollen Allergen Components and Cross-Reactive Carbohydrate Determinants in Mugwort-Sensitized Child Patients With Allergic Respiratory Disease in Western China - Liao, Chenxi; Hou, Xiangqing; Wu, Liting; Luo, Wenting; Zhang, Hong; Sun, Xin; Yu, Yongmei; Zhang, Xiaohua Douglas; Sun, Baoqing (Frontiers in Pediatrics, 2022)
Mugwort is a common pollen allergen in western China, and this study aimed to investigate the patterns of molecular sensitization to major grass pollen allergens (mugwort, ragweed, bermuda grass, and timothy grass) and cross-reactive carbohydrate determinants (CCD) in children who were sensitized to mugwort in western China. Serum-specific IgE (sIgE) of major allergen components and CCD were detected among 121 mugwort SPT-positive children via the EUROBlotMaster system if the mugwort-sIgE was positive (MSP). A CCD inhibition test was further performed on the serum of patients with positive CCD-sIgE. Latent class analysis was used to identify the patterns of potential sensitization to major grass pollen allergens. Of a total of 100 patients with mugwort-sIgE positive (MSP), 52.0, 41.0, and 31.0% of them were positive to Art v 1, Art v 3, and Art v 4, respectively. An optimal model with three latent classes was determined using grass pollen allergens, components, and CCD. The sensitization patterns can be summarized as (1) MSP and cosensitized to ragweed, bermuda grass, and timothy grass (23.74%); (2) MSP and cosensitized to Art v 1 (54.08%); (3) MSP and cosensitized to Art v 4, Cyn d 12, Phl p 12 (22.18%). Additionally, CCD sIgE levels had a significant positive correlation with ragweed, bermuda grass, and timothy grass (P < 0.05), and CCD-Inhibitor can highly inhibit the above allergens sIgE. Our findings suggest that Art v 4 was the typical cross-reaction component of mugwort, which is cosensitized to Phl p 12 and Cyn d 12. A wide cross-reaction among ragweed, bermuda grass, and timothy grass caused by CCD was observed.